Insights into engineering work for future surveyors - Mirzayev Jonibek Oltiyevich; Abduraxmonov Doniyorbek Ravshan o‘g‘li; Shukurullayev Sayfullo Dilshod o‘g‘li (International Journal of Economic Integration and Regional Competitiveness, 2024)
The article describes the conduct of geodetic work on engineering work by young specialists entering this field, and provides final conclusions and proposals for the work performed.